2007
DOI: 10.1128/jvi.01781-06
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Existence of the Loop E Motif of Potato Spindle Tuber Viroid In Vivo

Abstract: RNA motifs comprising nucleotides that interact through non-Watson-Crick base pairing play critical roles in RNA functions, often by serving as the sites for RNA-RNA, RNA-protein, or RNA small ligand interactions. The structures of viral and viroid RNA motifs are studied commonly by in vitro, computational, and mutagenesis approaches. Demonstration of the in vivo existence of a motif will help establish its biological significance and promote mechanistic studies on its functions. By using UV cross-linking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
1
18
0
4
Order By: Relevance
“…Lastly, our biochemical assays provide direct evidence that the secondary structure of PSTVd can be processed by DCLs into small RNAs. Importantly, there is evidence suggesting that the secondary structure of PSTVd exists in vivo (95,97,103). Thus, there is a solid basis for a structured PSTVd RNA to serve as a DCL substrate in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our biochemical assays provide direct evidence that the secondary structure of PSTVd can be processed by DCLs into small RNAs. Importantly, there is evidence suggesting that the secondary structure of PSTVd exists in vivo (95,97,103). Thus, there is a solid basis for a structured PSTVd RNA to serve as a DCL substrate in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…1A [43]). Importantly, there is evidence to suggest that the secondary structure of PSTVd exists in vivo (95,97,103), making it a compelling model to address the question of whether infectious RNA structures could be substrates for small RNA biogenesis in vivo.…”
mentioning
confidence: 99%
“…It has been shown to play a role in in vitro processing (Baumstark et al, 1997;Schrader et al, 2003) and host adaptation (Wassenegger et al, 1996;Qi and Ding, 2002;Zhu et al, 2002). Recent studies led to a precise tertiary structural model of PSTVd loop E and loss-offunction genetic evidence for its role in replication (Zhong et al, 2006) and demonstration of its existence in vivo (Eiras et al, 2007;Wang et al, 2007). A bipartite motif mediates PSTVd trafficking from bundle sheath to mesophyll in young tobacco leaves (Qi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ribosomal RNAs, where loop E motifs appear to organize multihelix loops (Leontis and Westhof 1998b), the central conserved region of CVd-III or PSTVd must ''switch'' from a multiloop processing structure to an extended structure containing a loop E motif. Zhong et al (2006) have recently shown how the isostericity matrices developed by Leontis et al (2002) can be used to rationalize tertiary-structure-function relationships involving the loop E motif of PSTVd and related viroids; furthermore, evidence has also been obtained for the existence of loop E in vivo (Wang et al 2007). Our results obtained with a more distantly related viroid indicate that this tertiary-structure-function relationship is yet more complex and contains an important dynamic component.…”
Section: Proposed Mechanism For Apscaviroid Processingmentioning
confidence: 99%